The Concept of the Hospital as a Business Institution in Health Services: Study during the Covid-19 Pandemic - Elli Ruslina (Institute of Computer Science (IOCS), 2021)
Hospital institutions are reflected in the enactment of Law Number 44 of 2009 concerning Hospitals. Article 18 of the Hospital Law divides the types of services and their management, the management of which is Public Hospital and Private Hospital. Public hospitals are managed by the government, local governments are non-profit. A private hospital in the form of a limited liability company is profit-oriented. This model actually refers to the behavior of companies that maximize profits. The form of Hospital by Laws can be Hospital Regulations, Standard Operating Procedures (SOP), Decrees, Assignments, Announcements, Notifications and Agreements (MOU). The arrangement is in line with Law Number 23 of 1992 concerning Health and its derivatives. How do public services against the emergence of the COVID-19 pandemic have an impact on daily life, which includes public services in the health sector. The purpose of this study is to analyze how hospital management with the concept of a profit-oriented business institution does not deviate from the concept of hospital social functions; and how can a hospital with a business model model provide good and affordable services to all levels of society, during the covid-19 pandemic? The method uses a normative juridical approach to the study of secondary data in the form of laws and regulations, research results, and articles. Data analysis was carried out in a juridical qualitative way. The results of the study, an important goal in hospital change is to increase efficiency and guarantee for the poor to get hospital services, so that changes will be measured by economic indicators and other indicators including the social function of hospitals. Covid-19 referral hospital services continue to serve Covid-19 patients, according to the strategy of the central and regional governments, the hospitals are selected based on the region.